Crushing strength prediction method and screening method for cigarette blast beads
Through the quality of the quality of the cigarettes, the quality characteristics of the smoke were obtained, and the multi -linear regression equation was established to predict the pressure breakage of the explosion beads to solve the problem of detecting and screening in existing technologies. The quality of cigarette products.
Patent Information
- Application Number
- CN202310923915.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art cannot detect the compressive strength of the explosive beads used for cigarettes one by one, resulting in the inability to screen out explosive beads that do not meet the requirements, affecting the quality of cigarette products.
Adopt the TPA mode and destructive test mode of the substitution, obtain multiple qualitative characteristics parameters for smoke, and establish a multi -linear regression equation to predict the pressure breakthrough of the explosion beads to achieve the destruction of the beads to be tested. 100%comprehensive detection.
Through the prediction method, you can detect the voltage breakthrough of explosion beads, screen out the explosive beads that meet the requirements, and improve the quality and production efficiency of cigarette products.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cigarette bursting beads detection, and in particular to a method for predicting and screening the crushing strength of cigarette bursting beads. Background Art
[0002] Cigarette popping beads are spherical capsules made of film-forming materials, also known as fragrant balls, brittle capsules, beads, etc. Cigarette popping beads are composed of a layer of rubber shell (wall material) wrapped with liquid (core material). Some products have coating films and are mainly used in cigarette filter rods to achieve artificially controllable release of characteristic flavors during cigarette smoking, enriching the taste of cigarette smoking.
[0003] During the filter rod forming and cigarette processing, the popping beads will be subjected to a certain degree of extrusion or impact. Therefore, the popping beads must have appropriate mechanical properties to ensure the adaptability of the popping beads to the machine during the filter rod forming and cigarette processing, and to avoid the popping beads from being broken, flattened or deformed when they are put on the machine. When consumers smoke popping bead cigarettes, they use their fingers to break the popping beads in the filter rod or their teeth to bite through them to achieve the sensory effect of "popping beads". Therefore, the popping beads must also have appropriate mechanical properties to ensure that consumers can crush or bite through the popping beads. In the prior art, the mechanical properties of the popping beads are generally characterized by the crushing strength. The detection of the crushing strength is based on the mechanical pressure method. The pressure sensor collects the instantaneous pressure value when the popping beads break, thereby obtaining the crushing strength of the popping beads. It is a destructive test.
[0004] The above method of testing the crushing strength is limited in sample size for random testing. There are still some bursting beads that do not meet the requirements among the untested bursting beads. If these bursting beads are used in filter rods or cigarettes, there may be quality problems such as breakage, flattening or deformation of the beads when the filter rods or cigarettes are put on the machine, thus affecting the quality of the bursting bead cigarette products.
[0005] In order to screen out bursting beads that meet the requirements and ensure the quality of bursting bead cigarettes, the present application provides a method for predicting the crushing strength of bursting beads for cigarettes and a method for screening them. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a method for predicting the crushing strength of tobacco bursting beads and a method for screening them, so as to solve the problems in the prior art that the bursting beads cannot be detected one by one and the bursting beads that do not meet the requirements cannot be screened out.
[0007] To achieve the above-mentioned and other related purposes, the present invention provides a method for predicting the crushing strength of a cigarette-use explosive bead, the method comprising the following steps:
[0008] Under the condition that the sample tobacco popping beads are not crushed, the sample tobacco popping beads are tested using the TPA (Texture Profile Analysis, abbreviated as TPA, hereinafter referred to as TPA) mode of the texture analyzer to obtain multiple texture characteristic parameters of the sample tobacco popping beads;
[0009] Using a texture analyzer to perform a destructive test on the sample tobacco bursting beads to obtain the crushing strength of the sample tobacco bursting beads;
[0010] Using the plurality of texture characteristic parameters as independent variables and the crushing strength as a dependent variable, a multivariate linear regression equation of the crushing strength is calculated;
[0011] Under the condition that the bursting beads for cigarettes to be tested are not crushed, the TPA mode of the texture analyzer is used to test the bursting beads for cigarettes to be tested, and multiple texture characteristic parameters of the bursting beads for cigarettes to be tested are obtained. The parameters are substituted into the multivariate linear regression equation to calculate the predicted crushing strength of the bursting beads for cigarettes to be tested.
[0012] It can be understood that the sample tobacco bursting beads used when the sample tobacco bursting beads are tested using the TPA mode of the texture analyzer and the sample tobacco bursting beads used when the sample tobacco bursting beads are destructively tested using the texture analyzer are the same bursting beads.
[0013] Preferably, the multiple texture characteristic parameters include the initial diameter of the tobacco bursting beads, adhesion, cohesion, initial modulus, target displacement, hardness, first extrusion work and first return work of the first extrusion process in the TPA mode, and the hardness, second extrusion work and second return work of the second extrusion process in the TPA mode.
[0014] It can be understood that the multiple texture characteristic parameters and the crushing strength are curves of the three basic parameters of real-time force, displacement and time obtained in the experimental process of testing the bursting beads by a texture analyzer. The following parameters are calculated through the above three basic parameter curves: the initial diameter of the bursting beads, adhesion, cohesion, and initial modulus, the target displacement, hardness, first extrusion work and first return work of the first extrusion process in the TPA mode, the hardness, second extrusion work, and second return work of the second extrusion process in the TPA mode, and the crushing strength.
[0015] The TPA mode uses the probe of the texture analyzer to squeeze the popping beads twice without damage.
[0016] Initial diameter: The diameter of the bead at the moment it is squeezed by the probe of the texture analyzer, expressed as the distance between the probe and the sample operating table (zero point) when the pressure reaches a certain value, in millimeters (mm);
[0017] Adhesion: The energy required to pull the probe out of the blasting bead after pressing down once, in Newton·millimeter (N·mm);
[0018] Cohesion: reflects the strength of the internal bonding of the bead. The lower the cohesion, the easier it is for the bead to split. It is the ratio of the second compression area to the first compression area under the two extrusion curves.
[0019] Initial modulus: When the blasting bead is initially squeezed, the resistance of the blasting bead to external squeezing, the slope when the stress increases linearly with the strain, the unit is Newton per millimeter (N / mm), the calculation formula is: Among them, F(5%) and F(20%) are the stresses when the bursting bead is deformed by 5% and 20% respectively, and H is the target displacement required to be generated according to the bursting bead size and deformation design value during the experiment;
[0020] Target displacement: the product of the initial diameter of the bursting bead and the deformation amount set by the test, in millimeters (mm);
[0021] Hardness: The ability of the bead to resist the probe from pressing into its surface. In the two extrusion processes, the bead will resist the extrusion of the probe twice, so there is a hardness parameter for each, which is the hardness in the first extrusion process and the hardness in the second extrusion process, and the unit is Newton (N).
[0022] The first (second) extrusion work: the work done by the probe when it squeezes the popping bead downward during the first (second) extrusion of the popping bead, the unit is Newton millimeter (N mm);
[0023] The work done during the first (second) return stroke is the work done by the probe during the upward return stroke during the first (second) squeezing of the bursting bead, in Newton·millimeter (N·mm);
[0024] Crushing strength: The pressure that a bursting bead withstands when it is squeezed and burst (broken) under specified conditions, measured in Newtons (N).
[0025] Preferably, the test conditions of the TPA mode of the texture analyzer include: a speed of 0.5 mm / s to 5.0 mm / s before the test, a test speed of 0.5 mm / s to 5.0 mm / s, a speed of 0.5 mm / s to 5.0 mm / s after the test, a trigger force of 0.05 N to 0.20 N, a time interval between two compressions of 0 s to 120 s, and a deformation amount of the tobacco bursting beads squeezed by 10% to 30%.
[0026] Preferably, the test conditions for performing destructive testing on the sample tobacco bursting beads using a texture analyzer include: a speed of 0.5 mm / s to 5.0 mm / s before the test, a test speed of 0.5 mm / s to 5.0 mm / s, a speed of 0.5 mm / s to 5.0 mm / s after the test, a trigger force of 0.05 N to 0.20 N, and a compression ratio of 60% to 90%.
[0027] Preferably, before testing the sample tobacco bursting beads or the tobacco bursting beads to be tested using the TPA mode of the texture analyzer, the sample tobacco bursting beads or the tobacco bursting beads to be tested are placed in a constant temperature and humidity chamber for at least 48 hours for equilibrium.
[0028] Preferably, the temperature of the constant temperature and humidity chamber is (22±1)°C, and the relative humidity is (60±3)%.
[0029] Preferably, when the sample tobacco bursting beads or the tobacco bursting beads to be tested are tested using a texture analyzer, the temperature is controlled to be (22±2)° C. and the relative humidity is controlled to be (60±5)%.
[0030] On the other hand, the present application provides a method for screening tobacco explosive beads, comprising:
[0031] The predicted bursting strength of the tobacco bursting beads to be tested is obtained according to the above-mentioned method for predicting the bursting strength of tobacco bursting beads;
[0032] The predicted bursting strength is compared with the preset bursting strength, the to-be-tested tobacco bursting beads with a strength greater than or less than the preset bursting strength are eliminated, and the to-be-tested tobacco bursting beads with a strength equal to the preset bursting strength are retained.
[0033] As described above, the present invention provides a method for predicting and screening the crushing strength of a cigarette-use explosive bead, which has the following beneficial effects:
[0034] The method for predicting the crushing strength of cigarette popping beads of the present application establishes a multivariate linear regression equation relationship between multiple texture characteristic parameters of sample popping beads and the crushing strength of sample popping beads. Without destroying the popping beads to be tested, 100% comprehensive testing can be performed on the popping beads to be tested. Multiple texture characteristic parameters of the popping beads to be tested are detected one by one, and the crushing strength of each popping bead to be tested is predicted by substituting the multiple linear regression equation relationship, thereby providing guidance for screening popping beads with suitable crushing strength.
[0035] The screening method for bursting beads for cigarettes of the present application calculates the predicted bursting strength of each bursting bead to be tested, and compares the predicted bursting strength with the preset bursting strength, eliminates the bursting beads outside the preset bursting strength range, screens out the bursting beads that meet the bursting strength requirements, and ensures the quality of the bursting bead cigarettes. DETAILED DESCRIPTION
[0036] The present application is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of protection of the present application.
[0037] The following describes the implementation of the present application through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. The present application can also be implemented or applied through other different specific implementations, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application.
[0038] The sample cigarette popping beads in the following examples are homemade popping beads; the texture analyzer is TMS-Pilot food physical property analyzer, FTC Company of the United States.
[0039] The present application embodiment provides a method for predicting the crushing strength of a cigarette bursting bead, comprising the following steps:
[0040] S100, using the Texture Profile Analysis (TPA, hereinafter referred to as TPA) mode and the single extrusion mode (bursting strength measurement mode) of the texture analyzer to measure the same sample of tobacco bursting beads successively, specifically including:
[0041] S101. Under the condition that the sample tobacco bursting beads are not crushed, the sample tobacco bursting beads are tested using the TPA mode of the texture analyzer to obtain multiple texture characteristic parameters of the sample tobacco bursting beads, wherein the multiple texture characteristic parameters include the initial diameter, adhesion, cohesion, initial modulus, target displacement, hardness, first extrusion work and first return work of the sample tobacco bursting beads in the first extrusion process in the TPA mode, and the hardness, second extrusion work and second return work of the second extrusion process in the TPA mode;
[0042] S102, using a texture analyzer in a crushing strength measurement mode to perform a destructive test on the sample tobacco bursting beads to obtain the crushing strength of the sample tobacco bursting beads;
[0043] S103, using the plurality of texture characteristic parameters as independent variables and the crushing strength as a dependent variable to calculate a multivariate linear regression equation of the crushing strength;
[0044] Among them, the multivariate linear regression equation can be obtained automatically by the system or by manual calculation;
[0045] S200, calculate the predicted crushing strength of the explosive bead for cigarettes to be tested:
[0046] Under the condition that the tobacco bursting beads to be tested are not crushed, the TPA mode of the texture analyzer is used to test the tobacco bursting beads to obtain a plurality of texture characteristic parameters of the tobacco bursting beads to be tested, and the parameters are substituted into the multivariate linear regression equation to calculate the predicted crushing strength of the tobacco bursting beads to be tested; wherein the plurality of texture characteristic parameters include the initial diameter, adhesion, cohesion, initial modulus of the tobacco bursting beads to be tested, the target displacement, hardness, first extrusion work and first return work of the first extrusion process in the TPA mode, and the hardness, second extrusion work and second return work of the second extrusion process in the TPA mode.
[0047] The present application also provides a method for screening tobacco explosive beads, comprising:
[0048] S300, obtaining the predicted crushing strength of the to-be-tested tobacco bursting bead according to the above-mentioned method for predicting the crushing strength of the tobacco bursting bead;
[0049] S400, comparing the predicted bursting strength with the preset bursting strength, eliminating the to-be-tested tobacco bursting beads that are not within the preset bursting strength range, and retaining the to-be-tested tobacco bursting beads that are within the preset bursting strength range.
[0050] Example 1
[0051] This embodiment provides a method for predicting and screening the crushing strength of cola popping beads, comprising the following steps:
[0052] S10, select sample blasting beads
[0053] Type of sample popping beads: Cola popping beads (diameter: 2.65mm~2.90mm);
[0054] Number of sample burst beads: 1000.
[0055] S20, sample bead bursting pre-treatment
[0056] In order to maintain the consistency and comparability of the test data, the sample cola burst beads were first placed in a constant temperature and humidity chamber for equilibrium for at least 48 hours. The temperature in the constant temperature and humidity chamber was (22±1)℃ and the relative humidity was (60±3)%.
[0057] S30. Test environment requirements
[0058] The environmental conditions for testing the cola popping beads sample using a texture analyzer were: controlled temperature at (22±2)°C and relative humidity at (60±5)%.
[0059] S40. Without crushing the sample cola popping beads, the sample cola popping beads were tested using the TPA mode of the texture analyzer, as follows:
[0060] After the sample cola popping beads are balanced, turn on the texture analyzer under the test environment of temperature (22±2)℃ and relative humidity (60±5)%, connect the 6mm diameter cylinder (model: TMS 6mm Steel), call the TPA mode, after the probe is zeroed, place a sample cola burst bead on the test platform, the probe moves downward at a speed of 0.5mm / s (speed before the test), and after touching the sample cola burst bead (trigger point, the trigger force reaches 0.2N), it continues to move downward at a speed of 2.5mm / s (test speed) to reach a compression distance of 30% (deformation 30%), and then the probe rises to the top of the sample (trigger point) at a speed of 0.5mm / s (speed after the test), recovers for 120s (the interval time between the two extrusion processes), and repeats the extrusion once, and records the three basic parameter curves of real-time force, displacement and time during the two extrusion operation tests. The initial diameter, adhesion, cohesion, initial modulus, target displacement, hardness, first extrusion work and first return work of the first extrusion process, hardness, second extrusion work and second return work of the second extrusion process are calculated through these three basic parameter curves.
[0061] S50. Use a texture analyzer to perform a destructive test on the sample cola popping beads to obtain the crushing strength of the sample cola popping beads, as follows:
[0062] Use a texture analyzer and call the single extrusion mode. For the cola beads sample after completing the step S40 test, the probe moves downward at a speed of 0.5 mm / s (speed before the test). After touching the cola beads sample (the trigger force reaches 0.2 N), it continues to move downward at a speed of 2.5 mm / s (test speed) until the cola beads sample ruptures (the compression ratio is set to 60%). Then the probe returns to the starting position at a speed of 0.5 mm / s (speed after the test), and records the three basic parameter curves of real-time force, displacement and time during the test and the crushing strength (or rupture strength) of the cola beads sample.
[0063] It can be understood that the sample cola bursting beads used in step S50 and the sample cola bursting beads used in step S40 are the same cola bursting beads, and the two tests are conducted on the same cola bursting beads.
[0064] Repeat step S40 and step S50 to complete the test of 1000 sample cola burst beads.
[0065] S60, using the multiple texture characteristic parameters of the 1000 sample cola popping beads obtained in step S40 as independent variables, and the crushing strength of the 1000 sample cola popping beads obtained in step S50 as the dependent variable, the system automatically calculates or manually calculates the multiple linear regression equation and the correlation coefficient R 2The multivariate linear regression equation is: bursting strength / N=(-1091970.902)×initial diameter of the bursting bead / mm+327615.4583×target displacement of the first extrusion process / mm+10.5910×hardness of the first extrusion process / N+(-42.5245)×work done in the first extrusion / (N·mm)+6.8768×work done in the first return stroke / N·mm+153.3185×adhesion / N+2.9460×hardness of the second extrusion process / N+(-7.7979)×work done in the second extrusion / (N·mm)+(-3.2956)×work done in the second return stroke / (N·mm)+16.0310×cohesion+1.6162×initial modulus / (N / mm)+(-65.9790), R 2 =0.9367. It can be seen that the correlation coefficient of the fitting equation is greater than 0.9, indicating that the crushing strength has a good linear relationship with the above-mentioned multiple texture characteristic parameters.
[0066] S70, online detection
[0067] Before testing the cola bursting beads to be tested, the cola bursting beads to be tested need to be pretreated. The pretreatment conditions are consistent with step S20, and the test environment is consistent with step S30. Use the TPA mode of the texture analyzer to test the cola bursting beads to be tested. Turn on the texture analyzer, connect a 6mm diameter cylinder (model: TMS 6mm Steel), call the TPA mode, and after the probe is zeroed, place a cola bursting bead to be tested on the test platform. The probe moves downward at a speed of 0.5mm / s (speed before the test), and after touching the cola bursting bead to be tested (trigger point, the trigger force reaches 0.2N), it continues to move downward at a speed of 2.5mm / s (test speed) to reach a compression distance of 30% (deformation 30%), and then the probe rises to the top of the sample (trigger point) at a speed of 0.5mm / s (speed after the test), recovers for 120s (the interval between the two extrusion processes), and then repeats the extrusion once. The three basic parameter curves of real-time force, displacement and time during the two extrusion operation tests are recorded, and the initial diameter, adhesion, cohesion, initial modulus, target displacement, hardness, first extrusion work and first return work of the first extrusion process, hardness, second extrusion work and second return work of the second extrusion process are calculated through the three basic parameter curves, and the multiple texture characteristic parameters of the cola bursting beads to be tested are substituted into the multiple linear regression equation obtained in step S60 to calculate the predicted crushing strength of the cola bursting beads to be tested;
[0068] S80, Reject
[0069] The predicted crushing strength of the cola beads to be tested was compared with the preset crushing strength, and the cola beads that met the requirements were screened out, and the cola beads that did not meet the requirements were rejected. For example, 8N≤preset crushing strength≤18N, the cola beads to be tested were screened, and the rejection rate of the cola beads to be tested was 3.86%.
[0070] Example 2
[0071] This embodiment provides a method for predicting and screening the crushing strength of peppermint popping beads, comprising the following steps:
[0072] S10. Select sample mint popping beads
[0073] Sample popping bead types: mint popping bead (diameter: 2.65mm~2.90mm);
[0074] Number of sample burst beads: 1000.
[0075] S20, sample mint bead pretreatment
[0076] In order to maintain the consistency and comparability of the test data, the sample mint bursting beads were first placed in a constant temperature and humidity chamber for equilibrium for at least 48 hours. The temperature in the constant temperature and humidity chamber was (22±1)℃ and the relative humidity was (60±3)%.
[0077] S30. Test environment requirements
[0078] The environmental conditions for testing the mint popping beads sample using a texture analyzer were: controlled temperature at (22±2)°C and relative humidity at (60±5)%.
[0079] S40. Without crushing the sample mint popping beads, the sample mint popping beads were tested using the TPA mode of the texture analyzer, as follows:
[0080] After the sample mint burst beads are balanced, turn on the texture analyzer under the test environment of temperature (22±2)℃ and relative humidity (60±5)%, connect the 6mm diameter cylinder (model: TMS 6mm Steel), call the TPA mode, after the probe is zeroed, place a sample mint burst bead on the test platform, the probe moves downward at a speed of 5mm / s (speed before the test), and after touching the sample mint burst bead (trigger point, the trigger force reaches 0.05N), it continues to move downward at a speed of 5mm / s (test speed) to reach a compression distance of 20% (deformation 20%), and then the probe rises back to the top of the sample (trigger point) at a speed of 5mm / s (speed after the test), and after recovering to 0s (the interval time between the two extrusion processes), repeat the extrusion once, and record the three basic parameter curves of real-time force, displacement and time during the two extrusion operation tests. The initial diameter, adhesion, cohesion, initial modulus, target displacement, hardness, first extrusion work and first return work of the first extrusion process, hardness, second extrusion work and second return work of the second extrusion process are calculated through these three basic parameter curves.
[0081] S50. Use a texture analyzer to perform a destructive test on the sample mint bursting beads to obtain the crushing strength of the sample mint bursting beads, as follows:
[0082] Use a texture analyzer and call the single extrusion mode. For the sample mint bursting beads after completing the step S40 test, the probe moves downward at a speed of 1.5 mm / s (speed before the test). After touching the sample tobacco bursting beads (the trigger force reaches 0.05 N), it continues to move downward at a speed of 2.5 mm / s (test speed) until the sample tobacco bursting beads break (the compression ratio is set to 90%). Then the probe returns to the starting position at a speed of 1.5 mm / s (speed after the test), and records the three basic parameter curves of real-time force, displacement and time during the test and the crushing strength (or rupture strength) of the sample mint bursting beads.
[0083] It can be understood that the sample mint popping beads used in step S50 and the sample mint popping beads used in step S40 are the same mint popping beads, and the two tests are conducted on the same mint popping beads.
[0084] Repeat steps S40 and S50 to complete the test of 1000 sample mint burst beads.
[0085] S60, using the multiple texture characteristic parameters of the 1000 sample mint popping beads obtained in step S40 as independent variables, and the crushing strength of the 1000 sample mint popping beads obtained in step S50 as the dependent variable, the system automatically calculates or manually calculates the multiple linear regression equation and the correlation coefficient R 2The multivariate linear regression equation is: bursting strength / N=(-842573.9307)×initial diameter of the bursting bead / mm+84205.0639×target displacement of the first extrusion process / mm+(-7.2693)×hardness of the first extrusion process / N+(-506.3610)×work done in the first extrusion / (N·mm)+93.5231×work done in the first return stroke / N·mm+8391.6698×adhesion / N+9.2151×hardness of the second extrusion process / N+592.8850×work done in the second extrusion / (N·mm)+(-25.7624)×work done in the second return stroke / (N·mm)+(-232.2677)×cohesion+2.0347×initial modulus / (N / mm)+292.7396, R 2 =0.9803. It can be seen that the correlation coefficient of the fitting equation is greater than 0.9, indicating that the crushing strength has a good linear relationship with the above-mentioned multiple texture characteristic parameters.
[0086] S70, online detection
[0087] Before testing the mint bursting beads to be tested, the mint bursting beads to be tested need to be pretreated. The pretreatment conditions are consistent with step S20, and the test environment is consistent with step S30. Use the TPA mode of the texture analyzer to test the mint bursting beads to be tested, turn on the texture analyzer, connect a 6mm diameter cylinder (model: TMS 6mm Steel), call the TPA mode, and after the probe is zeroed, place a mint bursting bead to be tested on the test platform. The probe moves downward at a speed of 5mm / s (speed before the test), and after touching the mint bursting bead to be tested (trigger point, the trigger force reaches 0.05N), it continues to move downward at a speed of 5mm / s (test speed) to reach a compression distance of 20% (deformation 20%), and then the probe rises back to the top of the sample (trigger point) at a speed of 5mm / s (speed after the test), and after recovering to 0s (the interval between the two extrusion processes), repeat the extrusion once and record it. Record the three basic parameter curves of real-time force, displacement and time during the two extrusion operation tests, calculate the initial diameter, adhesion, cohesion, initial modulus, target displacement, hardness, first extrusion work and first return work of the first extrusion process, hardness, second extrusion work and second return work of the second extrusion process, and substitute the obtained multiple texture characteristic parameters into the multivariate linear regression equation obtained in step S60 to calculate the predicted crushing strength of the mint bursting beads to be tested;
[0088] S80, Rejection:
[0089] The predicted crushing strength of the mint bursting beads to be tested was compared with the preset crushing strength, and the mint bursting beads that met the requirements were screened out, and the mint bursting beads that did not meet the requirements were rejected. For example, 8N≤preset crushing strength≤18N, and the mint bursting beads to be tested were screened, and the rejection rate of the mint bursting beads to be tested was 4.19%.
[0090] It can be understood that the test conditions for obtaining the multiple texture characteristic parameters of the tested tobacco bursting beads need to be consistent with the test conditions for obtaining the multiple texture characteristic parameters of the sample tobacco bursting beads.
[0091] Similarly, the multivariate linear regression equations between multiple texture characteristic parameters and the bursting strength of other types of popping beads can be obtained, and the correlation coefficients of the fitted equations are all greater than 0.9, further indicating that the bursting strength has a good linear relationship with multiple texture characteristic parameters. The popping beads can be tested online one by one without damaging them, and the popping beads that meet the requirements can be screened out, which improves the accuracy and precision of the screening and thus improves the quality of popping bead cigarettes.
[0092] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for predicting the crushing strength of a cigarette bursting bead, characterized in that: The prediction method comprises the following steps: Under the condition that the sample tobacco popping beads are not crushed, the sample tobacco popping beads are tested using the TPA mode of the texture analyzer to obtain multiple texture characteristic parameters of the sample tobacco popping beads; Using a texture analyzer to perform a destructive test on the sample tobacco bursting beads to obtain the crushing strength of the sample tobacco bursting beads; Using the plurality of texture characteristic parameters as independent variables and the crushing strength as a dependent variable, a multivariate linear regression equation of the crushing strength is calculated; Under the condition that the bursting beads for cigarettes to be tested are not crushed, the TPA mode of the texture analyzer is used to test the bursting beads for cigarettes to be tested, and multiple texture characteristic parameters of the bursting beads for cigarettes to be tested are obtained. The parameters are substituted into the multivariate linear regression equation to calculate the predicted crushing strength of the bursting beads for cigarettes to be tested.
2. The method for predicting the crushing strength of cigarette bursting beads according to claim 1, characterized in that: The multiple texture characteristic parameters include the initial diameter of the tobacco bursting beads, adhesion, cohesion, initial modulus, target displacement, hardness, first extrusion work and first return work of the first extrusion process in the TPA mode, and the hardness, second extrusion work and second return work of the second extrusion process in the TPA mode.
3. The method for predicting the crushing strength of cigarette bursting beads according to claim 1 or 2, characterized in that: The test conditions of the TPA mode of the texture analyzer include: a pre-test speed of 0.5 mm / s to 5.0 mm / s, a test speed of 0.5 mm / s to 5.0mm / s, the speed after the test is 0.5mm / s~5.0mm / s, the trigger force is 0.05N~0.20N, the time interval between two compressions is 0s~120s, and the deformation amount of the cigarette bursting bead is 10%~30%.
4. The method for predicting the crushing strength of cigarette bursting beads according to claim 1 or 2, characterized in that: The test conditions for using the texture analyzer to perform a destructive test on the sample tobacco explosive beads include: a pre-test speed of 0.5 mm / s to 5.0 mm / s, a test speed of 0.5 mm / s to 5.0 mm / s, a post-test speed of 0.5 mm / s to 5.0 mm / s, and a trigger force of 0.05 N to 0.20N, compression ratio is 60%~90%.
5. The method for predicting the crushing strength of cigarette bursting beads according to claim 1 or 2, characterized in that: Before testing the sample cigarette bursting beads or the cigarette bursting beads to be tested using the TPA mode of the texture analyzer, the sample cigarette bursting beads or the cigarette bursting beads to be tested are placed in a constant temperature and humidity chamber for at least 48 hours for equilibrium.
6. The method for predicting the crushing strength of cigarette bursting beads according to claim 5, characterized in that: The temperature of the constant temperature and humidity chamber is (22±1)°C, and the relative humidity is (60±3)%.
7. The method for predicting the crushing strength of cigarette bursting beads according to claim 1 or 2, characterized in that: When testing the sample tobacco bursting beads or the tobacco bursting beads to be tested using a texture analyzer, the temperature is controlled at (23±1)°C and the relative humidity is controlled at (60±5)%.
8. A method for screening explosive beads for cigarettes, characterized in that: include: The predicted crushing strength of the tobacco explosive bead to be tested is obtained according to the method for predicting the crushing strength of the tobacco explosive bead according to any one of claims 1 to 7; The predicted bursting strength is compared with the preset bursting strength, the to-be-tested tobacco bursting beads with a strength greater than or less than the preset bursting strength are eliminated, and the to-be-tested tobacco bursting beads with a strength equal to the preset bursting strength are retained.